The Implementation of Arabic Vocabulary Learning Strategies Design Based on Howard Gardner's Multiple Intelligences /Penerapan Desain Strategi Pembelajaran Kosa-Kata Bahasa Arab Berbasis Multiple Intelligences Howard Gardner - Nadhif, Nadhif (UIN Raden Mas Said Surakarta, 2021)
The students’ failure to catch learning information can be caused by some factors, such as the unsuitability between teacher’s teaching strategies and students’ learning strategies. This paper is motivated by some teachers who have difficulties in implementing multiple intelligences and their need for closeness to the design of multiple intelligence-based mufrodat learning strategies that facilitate students 'comprehension and strengthen students' memories as the main provision for mastering four Arabic language skills. Through qualitative literature research taken from books and previous research that had been analyzed using descriptive analysis, it is founded that the teachers’ difficulties in designing Multiple Intelligences-based learning strategies can be caused by two factors; the focus on determining activities based on one type of intelligence and one-way learning paradigm. The design of a multiple intelligence-based learning strategy contains three components; first, the design of learning activities that contains various types of intelligence, two, paradigms of two-way learning, and third, the existence of activities to facilitate students’ comprehension and strengthen students' mufrodat memory through the use of the highest learning modalities, linking material with life safety, packaging material with emotions and giving appreciation of student learning progress.